A Systematic Literature Review on Diabetes Diagnosis Management System (DDM-SYS) (International Journal of Engineering and Computer Science, 2017)
Diabetes mellitus has been a deadly and widespread disease majorly in Africa and Asia. A number of approaches have been employed in diagnosing this disease to provide awareness to patients who may have such. Several research work have been publishes and presented to look into a management system for its diagnosis. Some crucial elements are yet missing from some of these literatures. However, few reviews have been centered on this systematically and thoroughly, that is, none have performed review systematically capturing the entire crucial elements such as diabetes type addressed, control recommendation considered, main contributions and approach strengths. This have brought about the lack of sufficiently good context of operation. In this paper, we carried out a systematic review of existing literature concerning diabetes diagnosis management system in so as to present a summarized evidences regarding the issue and background for positioning new research activities appropriately.